Generation and evaluation of a recombinant genotype VII Newcastle disease virus expressing VP3 protein of Goose parvovirus as a bivalent vaccine in goslings - Wang, Jianzhong (Virus Res, 2015)
Newcastle disease virus (NDV) and Goose parvovirus (GPV) are considered to be two of the most important and widespread viruses infecting geese. In this study, we generated a recombinant rmNA-VP3, expressing GPV VP3 using a modified goose-origin NDV NA-1 by changing the multi-basic cleavage site motif RRQKR↓F of the F protein to the dibasic motif GRQGR↓L as that of the avirulent strain LaSota as a vaccine vector. Expression of the VP3 protein in rmNA-VP3 infected cells was detected by immunofluorescence and Western blot assay. The genetic stability was examined by serially passaging 10 times in 10-day-old embryonated SPF chicken eggs. Goslings were inoculated with rmNA-VP3 showed no apparent signs of disease and developed a strong GPV and NDV neutralizing antibodies response. This is the first study demonstrating that recombinant NDV has the potential to serve as bivalent live vaccine against Goose parvovirus and Newcastle disease virus infection in birds.